The absorption and field strength of HF waves reflected at oblique incident from F2 region in the ionosphere - Aydogdu, M.; Ozcan, O.; Guzel, E.; Canyilmaz, M. (Amer Inst Physics, 2007)
The absorption (L) of the wave in the ionosphere has been calculated. The wave (5.47 MHz) is transmitted from Ercis-Turkey (39.03(0)N, 43.37(0)E) and received at Elazig-Turkey (38.70(0)N, 39.20(0)E). The field strength of this wave is measured by ITU-Compliant HF Field Strength Monitoring Terminal, and the absorption L in the ionosphere has been calculated. It is observed that the field strength of the wave is least around noon time and it increases at night times at all seasons. The diurnal and seasonal variations of the calculated absorption L shows that the maximum absorption in the wave occurs around noon time. The behaviour of the diurnal and seasonal variations of the field strength of the wave can be explained with the diurnal and seasonal variations of the calculated absorption L in the ionosphere. To obtain the absorption L, a method is proposed in this paper, and it can be apply the radio waves propagations in the ionosphere.
6th International Conference of the Balkan-Physical-Union -- AUG 22-26, 2006 -- Istanbul, TURKEY
Keywords: electromagnetic wave propagation in ionosphere; field strength; absorption